THE INFLUENCE OF CHRISTIAN EDUCATION IN CURBING RELIGIOUS CONFLICTS AND TERRORISM IN NORTHERN NIGERIA - OLAITAN OYEDELE OLAOBA; DANIEL DAMILARE ADEYINKA (International Studies Journal)
The persistent religious conflicts and terrorism in Northern Nigeria have given peculiar Nigerians a cause for deep concern in recent times. The imminent of religious conflict is not really recent; it has been in the society for a long time. At least in the eyes of the general public, the modern revival of religion appears to be closely linked to the resurgence of violent acts that are justified by religion. Thus, the reasoning goes, it is imperative to reduce, neutralize, or completely eradicate religion's influence on public life. But this may not be out-rightly true a position, as it cannot be admitted realistic with a religious man. People wonder why religion which used to be the cohesive factor and core of national unity, peaceful co-existence and national development, has become a tool for political manipulation, violence, destruction of lives and properties in Nigeria in contemporary times. There is a loss of values and effective Christian Education could really curb religious conflict and terrorism in the northern Nigeria and Christian Religious Education curriculum which contains Character formation would be an instrument to educate and give an orientation that enhances curbing conflicts and terrorism.